Saluran Komunikasi Kelompok Berbasis Gender pada Komunitas Petani Sayuran Organik (Kasus di Megamendung Kabupaten Bogor Provinsi Jawa Barat) - K. Matindas; A.V.S. Hubeis; A. Saleh (Institut Pertanian Bogor, 2010)
In development, it is often mentioned that women are less active because of lack the opportunity to get access toagricultural information. Group communication is one channel through which agricultural information is obtained.Understanding the group communication channels selected by male and female farmers can help show separate dataof male and female farmers. The objectives of this study were (1) to analyze the characteristics of male and femalefarmers as the group types in the communities of organic vegetable farmers, (2) to analyze the differences in thematerials of agricultural information they look for, and (3) to identify the differences in seeking agriculturalinformation through group channels.The study was conducted in the sub-district of Sukagalih, District ofMegamendung, Regency of Bogor, with the survey method of descriptive analysis. It used the stratificationtechnique of disproportionate random sampling and obtained 30 male farmers and 30 female farmers of organicvegetables. The results indicate that agricultural information often sought by male farmers, were the aspects ofenvironment, production and harvesting because these were related to their productive activities on farmland.Meanwhile, women often looked for information on the aspect of harvesting, because they were active in theproductive activities on farmland. The group channels used by men to get agricultural information were farmergroups and social lottery groups. On the other hand women always use families as a group channels because theycould any time discuss with conveniently. The difference in the need for agricultural information between men andwomen is the aspects of environment, harvesting, post-harvesting, and institution. The difference in the groupchannels chosen by men and women is the farmer groups, social lottery groups, cooperation and families. Not all ofthe group channels are effective in giving agricultural information, knowledge and skills to both gender. Obtainingagricultural information is the need of men and women and is a cycle that continues to occur.